Complications after therapeutic plasma exchange within 24 hours - Bharti, Jyoti; Chandra, Tulika; Solanki, Archana; Singh, Ashutosh; Reedy, D. Himanshu; Agarwal, Mallika (International Journal of Advances in Medicine, 2023)
Background: By therapeutic apheresis is to remove a pathologic element from blood or to modulate cellular function. By this study we observed, complications after the therapeutic plasma exchange (TPE) within 24 hours with respect to patient’s demographic profiles and procedural variations. Methods: One-year prospective observational study conducted by the Department of Transfusion Medicine in collaboration with the Medicine Department, King George’s Medical University, Lucknow India. Results: In our study total of 60 cases and total of 150 TPE cycles were performed. Maximum mean age (36±4) was observed for cough and vomiting both and maximum mean BMI was observed followed for Infection at phlebotomy site (36.34±5.09). Maximum mean variation of hemoglobin was observed for vomiting (2.28±0.00), followed by internal bleeding. Maximum mean variation of activated partial thromboplastin time (aPTT) was observed for cough (22.05±0.34), followed by vomiting. Maximum mean variation of prothrombin time (PT) was observed for hypothermia (13.16±10.47), followed by internal bleeding. Maximum mean variation of S. creatinine was observed for abdominal discomfort (0.23±1.54), followed by vomiting. Maximum mean variation of systolic blood pressure (SBP) was observed for cough (7.00±5.20), followed by bipedal edema. Maximum mean variation of SpO2 was observed for death. Conclusions: Complication within 24 hours after the procedure was abdominal discomfort mainly in males with a correlation with body mass index (BMI). We observed significant positive association with complication versus APTT, PT, S. urea, S. creatinine, pulse, SBP, SpO2 and BMI. This emphasizes the decreasing trend of the complications with the increase in number of cycles.